Fat Intake in Overweight Adolescents with Health Belief Model Approach - Devi Eka Ratnasari; Eti Poncorini Pamungkasari; Sri Mulyani (Postgraduate, University of Mataram, 2023)
Obesity in childhood is associated with early mortality, psychiatric, and cardiometabolic comorbidities, and is likely to remain into adulthood. One of the most often utilized models in health-related research to describe and predict behavioral health is the Health Belief Model. The current research aims to ascertain the link between adolescent fat intake and all HBM components. The design of this study was cross-sectional. Purposive sampling was the sampling method, and 110 participants from 4 secondary schools were included. The research data were analyzed using SPSS 27. Measurement of fat intake using a 24-hour food recall interview with two repetitions on non-consecutive days. HBM measurement using questionnaires with 59 questions representing 6 HBM constructs. The bivariate test was performed with the Spearman and Pearson tests. Variables significantly related to fat intake are cues to action and self-efficacy. The higher the cues to action, the lower the adolescent fat intake. Likewise, the higher the self-efficacy, the less fat intake in adolescents. HBM-based education is needed to increase adolescents' perceptions and beliefs regarding health problems, especially overweight, to support handling overweight issues in adolescents.